When Spirit Comes to Mind: Furthering Transactional Analysis Understandings of Spirituality in Health and Psychopathology. (April 2016) - Mellacqua, Zefiro
Moving from the pioneering work of transactional analyst Muriel James (1981) on the human spirit, the author returns to Eric Berne's (1972) humanistic reflections on the problem of "man's essence or Self" (p. 438) as a basis for critically reviewing the best-known transactional analysis contributions on religious and nonreligious spirituality. Case material is used to argue that there is a need to advance the transactional analysis understanding of spirituality and its complex interfaces with religiosity and religious psychopathology. This is important because such factors are often responsible for both the existential dilemmas and more practical challenges clinicians face when dealing relationally with patients' religious and spiritual experiences.